Revisiting the measure of development: A critique of sustainametrics - Okui, Go; Takeda, Shutaro (Frontiers in Sustainability, 2022)
For sustainametrics to gain a firm ground as an effective concept, the meaning of development shall be revisited first without depending on any statistical measurement. The word “development” originally meant the act of disclosure or opening a cover to disclose what is inside. Martin Heidegger (1889–1976) analyzed the significance of alētheuein, or “to bring the world out of its hidden and covered state and into ours,” and explicates that the alētheia under the condition of modern technology is dominated by a mode of revealing that is destructive to the earthly beings. Here, the danger inherent in the essence of technology, i.e., enframing [Ge-stell], renders human beings incapable of encountering the essence of beings as they are challenged and demanded to frame everything they encounter, including themselves, as mere variables. In contrast to Heidegger's thinking as releasement [Gelassenheit], Hannah Arendt's (1906–1975) conception of disclosure is closely tied to action. Following Heidegger's and Arendt's threads of thought, the authors conclude that any measures of development must be fundamentally grounded in disclosure through speech and action in the public realm. In this respect, the experts on the sustainametrics shall inspire fellow citizens to join the discourse by taking the risk of acting and speaking in public, disclosing who they are and what it is really meant for us. The course of development must ultimately be grounded in such an act of disclosure, only through which we may find something worth sustaining in our future development, and sustainametrics is no exception.